Pengaruh Ice Breaking terhadap Kinerja Kognitif dan Emosional Siswa - Azizi; Fathor Rosi; Muhammad Rizky (Khatulistiwa Insight: Islamic Education and Learning, 2025)
The application of ice breaking techniques in educational settings is increasingly recognized for its positive effects on cognitive and emotional performance. This study aimed to evaluate the impact of ice breaking on students' cognitive and emotional performance at MA Nurul Huda AL-Banat, focusing on the relationship between ice breaking activities and students' cognitive engagement, emotional state, and anxiety levels. A quasi- experimental design was employed with a pretest-posttest control group design, involving 30 students in the experimental group (who received the ice breaking treatment) and 30 students in the control group (who did not). Results from cognitive tests, emotional performance scales, and anxiety measures indicated significant improvements in the experimental group compared to the control group. The application of ice breaking significantly reduced anxiety, increased cognitive retention, and improved emotional engagement. These findings underscore the importance of incorporating ice breaking as an effective tool for enhancing both the cognitive and emotional aspects of learning, fostering a more inclusive and productive learning environment